The Impact of COVID-19 Pandemic on Seafood Safety and Human Health - Rathod, Nikheel Bhojraj; Elabed, Nariman; Özogul, Fatih; Regenstein, Joe M.; Galanakis, Charis M.; Aljaloud, Sulaiman Omar; Ibrahim, Salam A. (Frontiers in Microbiology, 2022)
The coronavirus disease (COVID-19) pandemic caused several negative impacts on global human health and the world's economy. Food and seafood safety and security were amongst the principal challenges and causes of concern for the food industry and consumers during the spread of this global pandemic. This article focused on the effects of COVID-19 pandemic on potential safety issues with seafood products and their processing methods. Moreover, the potential impacts of coronavirus transmission through seafood on human health were evaluated. The role of authenticity, traceability, and antimicrobials from natural sources to preserve seafood and the possible interaction of functional foods on the human immune system are also discussed. Although seafood is not considered a principal vector of SARS-CoV-2 transmission, the possible infections through contaminated surfaces of such food products cannot be neglected. The positive effects of seafood consumption on possible immunity built up, and COVID-19 are also summarized.